An attempt for empowering education: A qualitative study of in-service training of nursing personnel - Mahmood Chaghari; Abbas Ebadi; Ahmad Ameryoun; Mohsen Safari (Wolters Kluwer Medknow Publications, 2016)
Background: In-service training of nursing personnel has a significant role in increasing the empowerment of nurses and promotion of the quality of health services. The objective of this study is to identify and explain the process of in-service training of nursing personnel in the hospitals affiliated with Baqiyatallah University of Medical Sciences in Tehran. Materials and Methods: The present study employed a qualitative approach using Corbin and Strauss method (2008) in 2015, and examined the viewpoints and experiences of 35 nurses, nurse managers, and educational managers with the in-service education of nursing staffs. According to this method, comparisons, asking questions, flip-flop technique, depicting personal experiences, and raising red flag were used for data analysis. Results: In this study, five major themes including unsuccessful mandatory education, empowering education, organizational challenges, weakness in the educational management, and educational-job resiliency were derived from the results. Unsuccessful mandatory education was the main concern of participants and empowering education was the core category derived from this study. Conclusions: Empowering education emphasizes the practice-oriented and self-directed training. It is an applied education, is participation-oriented, facilitates job functions, and is based on exploration.